Investigation on the load-bearing capacity and joint formation of hybrid functional components joined by orbital forming - Hetzel, Andreas; Wituschek, Simon; Römisch, David; Sippel, Frank; Lechner, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part E-Journal of Process Mechanical Engineering, 2024)
Increasing material costs, decreasing availability, and ever-higher demands on environmental compatibility and complexity require new strategies in the development and production of functional components. Consequently, a combined approach from the areas of design, material science, and manufacturing is mandatory, in order to meet the requirements. Reducing the number of parts, using lightweight materials and applying hybrid components with a multimaterial mix are possible solutions. Nevertheless, conventional joining operations like welding or riveting are reaching their limits in terms of material utilization, load-bearing capacity as well as versatility of the process. Thus, innovative and versatile joining by forming operations and process combinations are focus of current research. In this context, the innovative process of orbital forming had been investigated as a joining by forming operation to manufacture load-adapted hybrid functional components. By tilting of one tool component during the process, a radial material flow is generated, allowing the crimping of the two joining partners. Nevertheless, the load-bearing capacity in axial direction could be identified as limiting factor for a possible application. Therefore, the aim of this investigation is the development of a fundamental process understanding on the influence of a novel geometrical adaption of the joint on the resulting load bearing capacity. The influence of varying geometrical proportions of the joint on the quality is evaluated, considering the form filling, the geometrical properties of the components as well as the maximum transmittable axial load. As joining partners, the dual-phase steel DP600 and the aluminum alloy EN AW-5754 with a thickness of 2.0 mm are use